Amyloid peptides ABri and ADan show differential neurotoxicity in transgenic Drosophila models of familial British and Danish dementia - Marcora, Maria Silvina (2014)
BACKGROUND: Familial British and Familial Danish dementias (FBD and FDD, respectively) are associated with mutations in the BRI2 gene. Processing of the mutated BRI2 protein leads to the accumulation in the brain of the 34-mer amyloid Bri (ABri) and amyloid Dan (ADan) peptides, accompanied by neurofibrillary tangles. Recently, transgenic mice successfully reproduced different aspects of FDD, while modeling of FBD in vivo has been more difficult. In this work we have modeled FBD and FDD in Drosophila and tested the hypothesis that ABri and ADan are differentially neurotoxic. RESULTS: By using site-directed insertion, we generated transgenic lines carrying ABri, ADan, Bri2-23 (the normal product of wild-type BRI2 processing) and amyloid-β (Aβ) 1-42 as a well-characterized neurotoxic peptide, alone or with a His-tag. Therefore, we avoided random insertion effects and were able to compare levels of accumulation accurately. Peptides were expressed with the GAL4-Upstream Activating Sequence (UAS) system using specific drivers. Despite low levels of expression, toxicity in the eye was characterized by mild disorganization of ommatidia and amyloid peptides accumulation. The highest toxicity was seen for ADan, followed by Aβ42 and ABri. Pan-neuronal expression in the CNS revealed an age-dependent toxicity of amyloid peptides as determined by the ability of flies to climb in a geotaxis paradigm when compared to Bri2-23. This effect was stronger for ADan, detected at 7 days post-eclosion, and followed by ABri and Aβ42, whose toxicity became evident after 15 and 21 days, respectively. Histological analysis showed mild vacuolization and thioflavine-S-negative deposits of amyloid peptides. In contrast, the over-expression of amyloid peptides in the specific subset of lateral neurons that control circadian locomotor activity showed no toxicity. CONCLUSIONS: Our results support the differential neurotoxicity of ADan and ABri in the Drosophila eye and CNS at low expression levels. Such differences may be partially attributed to rates of aggregation and accumulation. In the CNS, both peptides appear to be more neurotoxic than wild-type Aβ42. These Drosophila models will allow a systematic and unambiguous comparison of differences and similarities in the mechanisms of toxicity of diverse amyloid peptides associated with dementia.